Shift workers’ experiences and views of sleep disturbance, fatigue and healthy behaviors: a systematic review and qualitative evidence synthesis - Jack S Benton; Charlotte L Lee; Hannah A Long; Thavapriya Sugavanam; Leah Holmes; Annie Keane; Neal Thurley; Simon Kyle; David Ray; David P French (Scandinavian Journal of Work, Environment & Health)

(untitled)
OBJECTIVE: Shift work is common across most societies but poses significant risks to the health of shift workers. In part, this risk is due to the disruption of healthy sleep-wake schedules. This systematic review identified qualitative research on shift workers’ experiences of sleep disturbance, fatigue and healthy behaviors. METHODS: We conducted a systematic search of four databases (CINAHL, EMBASE, MEDLINE, PsycINFO) and identified 28 eligible studies involving 1519 participants. We appraised the studies using an adapted Critical Appraisal Skills Programme (CASP) checklist, and confidence in the review findings was formally assessed using the Grading of Recommendations Assessment, Development and Evaluation-Confidence in the Evidence from Reviews of Qualitative research (GRADE‐CERQual) approach. Data were thematically synthesized. RESULTS: Three analytical themes were generated. ‘Inevitability of fatigue and tiredness’ outlines how shift workers experience a culture where they feel “peer pressure to soldier through” their shifts regardless of fatigue. ‘Balancing sleep needs with competing responsibilities’ highlights how shift workers struggle to balance the need for daytime sleep with family, leisure, and work responsibilities, often prioritizing family needs over their own sleep. ‘Obstacles to engaging in healthy behaviors’ describes how shift workers often know which actions would benefit their health and reduce fatigue but find it challenging to translate this knowledge into behavior due to fatiguing and stressful work environments. For the purposes of the GRADE-CERQual assessment, short summary statements were developed to describe 22 review findings: there was moderate or high confidence in all but one of these findings. CONCLUSION: This review suggests that sleep education alone is unlikely to be effective. Interventions should focus on helping shift workers self-regulate their behaviors, thoughts, and emotions to better manage sleep and fatigue.